2008
DOI: 10.1007/s00535-008-2217-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of nuclear factor-κB in the effect of angiotensin II in the paraventricular nucleus in protecting the gastric mucosa from ischemia-reperfusion injury in rats

Abstract: NF-kappaB plays a role in PVN Ang II-mediated protection against GI-R injury. These central effects of Ang II are mediated by AT1 receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…microinjection of Ang II into the PVN inhibited mucosal injury in gastric ischemia-reperfusion induced ulcer model in a dose-dependent manner. The underlying mechanism is the increase of gastric blood flow, which effect turned to be mediated by central AT 1 receptors (Zhang et al, 2008). Moreover, reversal of the elevated mucosal level of NF-kappaB during gastric ischemia-reperfusion by Ang II may contribute to the Ang II-induced protection against injury (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…microinjection of Ang II into the PVN inhibited mucosal injury in gastric ischemia-reperfusion induced ulcer model in a dose-dependent manner. The underlying mechanism is the increase of gastric blood flow, which effect turned to be mediated by central AT 1 receptors (Zhang et al, 2008). Moreover, reversal of the elevated mucosal level of NF-kappaB during gastric ischemia-reperfusion by Ang II may contribute to the Ang II-induced protection against injury (Zhang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported that experimental gastric stress ulcerations may be prevented by the administra-tion of AT1 receptor blocking compounds both systemically and centrally (Pavel et al 2008, Zhang et al 2008a,b, Merai et al 2009). This mucosa protective effect has been proposed to be due to AT1 receptor mediated modulation of inflammatory factors, reduction of sympathetic neural activity and preservation of gastric mucosal blood perfusion (Pavel et al 2008).…”
Section: Mucosal Ulcerationsmentioning
confidence: 99%
“…When NF-kB translocates to the nucleus, it activates the transcription genes related to inflammatory response. It has been reported that NF-kB is activated and translocated during I/R in the stomach [18]. Whether Ang II can regulate gastric ischemia reperfusion injury is not known for its possible molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%